1993
DOI: 10.3109/00016489309135882
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Bacterial Culture from Adenoid Lymphatic Tissue with Special Reference toHaemophilus influenzaeAge-associated Changes

Abstract: Homogenized adenoid tissue from 55 children (28-153 months) undergoing adenoidectomy because of nasopharyngeal obstruction was investigated by means of quantitative aerobic bacterial culture. The children were divided into two groups, the hypertrophy alone group--AH (n = 29)--and the hypertrophy with longstanding secretory otitis media group--SOM (n = 26). A nasopharyngeal culture was obtained preoperatively from 38 of the cases. Non-typeable H. influenzae (NTHI) was found in twice as many cases in the AH grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In a recent study of bacterial load on homogenized adenoid lymphatic tissue, H. infiuenzae was found in only 50% of the nasopharyngeal cultures corresponding to a positive quantitative culture. This suggests that bacteria are harboured in crypts or in the lymphatic tissue [22]. In a recent study it has been possible to demonstrate H. infiuenzae intracellularly in macrophages by electron microscopy and by RNA hybridization [23].…”
Section: Dlsctsslonmentioning
confidence: 99%
“…In a recent study of bacterial load on homogenized adenoid lymphatic tissue, H. infiuenzae was found in only 50% of the nasopharyngeal cultures corresponding to a positive quantitative culture. This suggests that bacteria are harboured in crypts or in the lymphatic tissue [22]. In a recent study it has been possible to demonstrate H. infiuenzae intracellularly in macrophages by electron microscopy and by RNA hybridization [23].…”
Section: Dlsctsslonmentioning
confidence: 99%
“…9 Most published studies of adenoid bacteriology have investigated the bacteriology of the adenoid surface rather than its core. 10,11 The present study sought to address this issue, and to assess the correlation between the bacteriology of paediatric sinusitis and the prevalence of bacterial pathogens in the adenoid core.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative bacterial studies have shown that nontypeable H. influenzae is isolated from homogenized adenoid tissues more often than from nasopharyngeal cultures in the same individual, suggesting that this organism is harbored within the adenoids [18]. SIgA can inhibit initial pathogen colonization through immune exclusion, both on the mucosal surface and within virusinfected secretory epithelial cells, and it can block microbial toxins and other antigens.…”
Section: Discussionmentioning
confidence: 99%